Climate as the Main Driver of Large‐Scale Genetic Patterns and Connectivity in the Expanding Golden Jackal - Alejandro Flores‐Manzanero; Wiesław Bogdanowicz; Milomir Stefanović; Roya Adavoudi; Rasoul Khosravi; Francelly Martínez‐Sosa; Karolina Doan; Yellapu Srinivas; Ovidiu C. Banea; Duško Ćirović; Gianluca D'Amico; Mihajla Djan; et al. (Global Change Biology, 2026)
Rapid global changes in climate and habitats lead to shifts in species' geographic ranges. Range contractions experienced by numerous species may result in local extinctions and connectivity disruptions. In some species, range expansions have been observed instead, suggesting the enlargement of suitable habitats and/or adaptations to changing environments. Despite its importance for wildlife management, our understanding of the factors influencing species' spatial responses to rapidly changing environments remains limited. The golden jackal serves as an excellent model to address this knowledge gap, given its ongoing rapid range expansion. In this study, we investigated environmental factors contributing to genetic connectivity and local adaptation across the expanding range of the golden jackal, based on a comprehensive sampling scheme across Eurasia ( n = 363), a high‐quality set of genomic markers (19,746 SNPs), and a landscape genomics framework. At the continental scale, geographic distance emerged as the predominant factor. At finer spatial scales, genetic connectivity was best explained by climatic predictors, specifically high annual and seasonal variations in precipitation and temperature, which can shape the species' spatial genetic structure by constraining gene flow. Our connectivity models for current and future climatic conditions show that the species' northward expansion is facilitated by changes in these variables in central and northern Europe promoting high connectivity. Precipitation and temperature were also responsible for most local adaptation signals. Given the potential role of hybridization with domestic dogs in shaping range expansion patterns, we investigated the association between environmental conditions and dog admixture proportions. We found no significant trends, indicating a limited effect of dog admixture on habitat choice. Collectively, our findings suggest that the golden jackal has the potential to continue its expansion across Eurasia in response to ongoing global climate change, providing an example of a species that rapidly tracks the expansion of its suitable habitats.

NW-MEXVEL: a GPS-based crustal deformation model using green’s functions for Northwestern Mexico - Daniel Hernández-Andrade; María Clara de Lacy Pérez-de los Cobos; Rosendo Romero-Andrade; Gabriel Auvinet-Guichard; Edgar Méndez-Sánchez; Manuel Edwiges Trejo-Soto (Applied Geomatics, 2026)
The research examines and describes the interaction between the Pacific and North American Plates in Northwest Mexico using 12 years (2010–2021) of Global Positioning System (GPS) data from 33 continuously operating reference stations, processed by GAMIT/GLOBK. A bidimensional crustal deformation model was developed on a 15’ x 15’ grid, based on Green’s functions and elastic coupling. The proposed model NW-MEXVEL has been evaluated by direct point-to-point validation using the GEODVEL global model as a reference. The displacements obtained in the NW-MEXVEL model, adjusted to the ITRF14, are reliable for movements greater than 1.6 mm yr −1 based on the root mean square error (RMSE) of modeled velocities compared to measured velocities. The RMSE values are similar for each tectonic plate, including the Gulf of California Islands (Angel and Tiburon) and Guadalupe Island on the Pacific Plate. This consistency is attributed to the use of regional data from critical zones, in contrast to the global tectonic model. Finally, velocity fields revealed an average displacement of 44.72 ± 0.29 mm yr −1 in the Northwest direction for the Pacific Plate fixed to the North American Plate and 45.34 ± 0.18 mm yr −1 in the Southeast direction for the North American Plate fixed to the Pacific Plate. These velocity results are in agreement with previous studies.

On the transport of CO 2 and Radon in the geothermal area of Acoculco, Puebla, Mexico - Fernando J. Guerrero; Daniel Pérez-Zárate; Edgar Santoyo; Adrián Jiménez-Haro; David Yáñez-Dávila; Gustavo Santos-Raga (Journal of Volcanology and Geothermal Research, 2025)

Exposure to silver, aluminium, arsenic, cadmium, mercury, nickel and lead from food in Swedish children, adolescents and adults - Helena Bjermo; Daniel Edgar; Sanna Lignell; Barbro Kollander (Food and Chemical Toxicology, 2025)

Optimizing machine learning models for cytotoxicity prediction in lanthanide-doped nanomaterials: A data-driven approach for minimizing environmental hazards - Edwin E. Reza-Zaldívar; Jorge L. Mejía-Méndez; Diego E. Navarro-López; A. Sanchez-Martinez; O. Ceballos-Sanchez; Vicente Rodríguez-González; Miriam Irene Jiménez-Pérez; L. Marcelo Lozano; Juan Armendariz-Borunda; Daniel A. Jacobo-Velázquez; Gildardo Sanchez-Ante; Edgar R. López-Mena (Journal of Hazardous Materials, 2025)

Chemical characterization, nutritional profile, and cytotoxicity potential of Amazonian Theobroma sylvestre Mart. fruits - Edson Queiroz da Fonseca Júnior; Daniel de Queiroz Rocha; Edinilze Souza Coelho Oliveira; Samuel Oliveira da Silva; Francisca das Chagas do Amaral Souza; Gabriela Furlaneto; Laura da Silva Cruz; Luciana Azevedo; Renilto Frota Corrêa; Edgar Aparecido Sanches; Pedro Henrique Campelo; Jaqueline de Araújo Bezerra (Food Bioscience, 2025)

Network of networks: Time series clustering of AmeriFlux sites - David E Reed; Housen Chu; Brad G. Peter; Jiquan Chen; Michael Abraha; Brian Amiro; Ray G. Anderson; M. Altaf Arain; Paulo Arruda; Greg A. Barron-Gafford; Carl Bernacchi; Daniel P. Beverly; et al. (Agricultural and Forest Meteorology, 2025)

Primate teeth are good proxies for understanding past water inputs and seasonality - Tanya M. Smith; Janaína N. Ávila; Jelmer W. Eerkens; Daniel R. Green; Katie Hinde; Edgar Huerta; Paul Tafforeau; Ian S. Williams (Geochimica et Cosmochimica Acta, 2025)

Molecular dynamics study of the helix-to-disorder transition in short antimicrobial peptides from Urodacus yaschenkoi - Flora Fernandez-Sánchez; Jenny Flores-Ávila; Hugo S. García; Edgar Mixcoha; Daniel Balleza (European Biophysics Journal, 2025)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Resilient plants, sustainable future - Seung Y. Rhee; Daniel N. Anstett; Edgar B. Cahoon; Alejandra A. Covarrubias-Robles; Eric Danquah; Natalia Dudareva; Hiroshi Ezura; Kadeem J. Gilbert; Rodrigo A. Gutiérrez; Michelle Heck; David B. Lowry; Ron Mittler; et al. (Trends in Plant Science, 2025)

Identification of purinergic system components in the venom of Bothrops mattogrossensis and the inhibitory effect of specioside extracted from Tabebuia aurea - Dhébora Albuquerque Dias; Kamylla Fernanda Souza de Souza; Iluska Senna Bonfá Moslaves; Marcus Vinicius Buri; Denise Caroline Luiz Soares Basilio; Isabelly Teixeira Espinoça; Eduardo Benedetti Parisotto; Saulo Euclides Silva-Filho; Ludovico Migliolo; Jeandre Augusto Otsubo Jaques; Daniel Guerra Franco; Ana Marisa Chudzinski-Tavassi; et al. (Purinergic Signalling, 2025)

Microplastics in marine fish: a mini-review on presence, classification, and impacts - María Timaná Morales; Viridiana Peraza Gómez; Eva R. Kozak; José Vladimir Trejo Flores; Maricruz Robles Ravelero; Luis Daniel Espinosa Chaurand; Edgar Iván Jiménez Ruíz (Ecotoxicology, 2025)

Dose-related effects of eugenol: Exploring renal functionality and morphology in healthy Wistar rats - Renner Philipe Rodrigues Carvalho; Rosiany Vieira da Costa; Isadora Ribeiro de Carvalho; Arabela Guedes Azevedo Viana; Camilo Ramirez Lopez; Mariana Souza Oliveira; Luiz Otavio Guimarães-Ervilha; Wassali Valadares de Sousa; Daniel Silva Sena Bastos; Edgar Diaz Miranda; Fábio César Sousa Nogueira; Mariana Machado-Neves (Food and Chemical Toxicology, 2025)

Nano versus bulk: Evaluating the toxicity of lanthanum, yttrium, and cerium oxides on Enchytraeus crypticus - Joana Santos; Inês Neca; Ana Capitão; João Nogueira; José A.S. Santos; Edgar Pinto; Angela Barreto; Ana L. Daniel-da-Silva; Vera L. Maria (NanoImpact, 2025)

Retraction notice to “Toxicity of spike fragments SARS-CoV-2 S protein for zebrafish: A tool to study its hazardous for human health?” [Sci. Total Environ. 813 (2022) / 152345] - Bianca H. Ventura Fernandes; Natália Martins Feitosa; Ana Paula Barbosa; Camila Gasque Bomfim; Anali M.B. Garnique; Ivana F. Rosa; Maira S. Rodrigues; Lucas B. Doretto; Daniel F. Costa; Bruno Camargo-dos-Santos; Gabrielli A. Franco; João Favero Neto; et al. (Science of The Total Environment, 2024)

First national mapping of cadmium in cacao beans in Colombia - Daniel Bravo; Gustavo Araujo-Carrillo; Fabricio Carvalho; Nesrine Chaali; Clara León-Moreno; Ruth Quiroga-Mateus; Santiago Lopez-Zuleta; Omar Domínguez; Paula Arenas; Edgar Avella (Science of The Total Environment, 2024)

Monitoring drift and associated biodiversity of nearshore rafts of holopelagic Sargassum spp. in the Mexican Caribbean - Brigitta I. van Tussenbroek; L. Verónica Monroy-Velázquez; Dení Rodríguez; L. Parmenio Suescún-Bolívar; Patricia E. Thomé; Daniel Cerqueda-García; José Q. García-Maldonado; Isis G. Martínez-López; José Antonio López-Portillo; M. Guadalupe Barba-Santos; Miguel Angel Gómez-Reali; J. Edgar Escalante-Mancera (Aquatic Botany, 2024)

Evaluation of a Biodegradable and Sprayable Mulch Material for Weed Control in Vineyards and Orchards - Swen Follak; Michael Kirchinger; Anja Menger; Markus Redl; Arno Schmid; Daniel Heßdörfer; Ewald Lardschneider; Edgar Remmele; Monika Riedle-Bauer; Franz Rosner; Siegrid Steinkellner; Silvia Winter; et al. (Applied Fruit Science, 2024)

Dominance and rarity in tree communities across the globe: Patterns, predictors and threats - Iris Hordijk; Lalasia Bialic‐Murphy; Thomas Lauber; Devin Routh; Lourens Poorter; Malin C. Rivers; Hans ter Steege; Jingjing Liang; Peter B. Reich; Sergio de‐Miguel; Gert‐Jan Nabuurs; Javier G. P. Gamarra; et al. (Global Ecology and Biogeography, 2024)
Aim Ecological and anthropogenic factors shift the abundances of dominant and rare tree species within local forest communities, thus affecting species composition and ecosystem functioning. To inform forest and conservation management it is important to understand the drivers of dominance and rarity in local tree communities. We answer the following research questions: (1) What are the patterns of dominance and rarity in tree communities? (2) Which ecological and anthropogenic factors predict these patterns? And (3) what is the extinction risk of locally dominant and rare tree species? Location Global. Time period 1990–2017. Major taxa studied Trees. Methods We used 1.2 million forest plots and quantified local tree dominance as the relative plot basal area of the single most dominant species and local rarity as the percentage of species that contribute together to the least 10% of plot basal area. We mapped global community dominance and rarity using machine learning models and evaluated the ecological and anthropogenic predictors with linear models. Extinction risk, for example threatened status, of geographically widespread dominant and rare species was evaluated. Results Community dominance and rarity show contrasting latitudinal trends, with boreal forests having high levels of dominance and tropical forests having high levels of rarity. Increasing annual precipitation reduces community dominance, probably because precipitation is related to an increase in tree density and richness. Additionally, stand age is positively related to community dominance, due to stem diameter increase of the most dominant species. Surprisingly, we find that locally dominant and rare species, which are geographically widespread in our data, have an equally high rate of elevated extinction due to declining populations through large‐scale land degradation. Main conclusions By linking patterns and predictors of community dominance and rarity to extinction risk, our results suggest that also widespread species should be considered in large‐scale management and conservation practices.

Automated SEM analysis of particles in Hanford tank waste - Jarrod R. Allred; Edgar C. Buck; Richard C. Daniel; John G.H. Geeting; Amy M. Westesen; Reid A. Peterson (Journal of Hazardous Materials, 2024)

The socioecological benefits and consequences of oil palm cultivation in its native range: The Sustainable Oil Palm in West Africa (SOPWA) Project - Michael D. Pashkevich; Cicely A.M. Marshall; Benedictus Freeman; Valentine J. Reiss-Woolever; Jean-Pierre Caliman; Julia Drewer; Becky Heath; Matthew T. Hendren; Ari Saputra; Jake Stone; Jonathan H. Timperley; William Draper; et al. (Science of The Total Environment, 2024)

The influence of lithospheric inheritance and Cenozoic magmatism on Phanerozoic rock cooling in the São Francisco Craton and adjacent orogens - Edgar do Amaral Santos; Andréa Ritter Jelinek; Frederico Antônio Genezine; Daniel Stockli (Gondwana Research, 2024)

Environmental-related applications of ZnO nanopowders: Photocatalytic activity and photoluminescence response to ethanol - Oscar Marin-Ramirez; Matias Cornet; Daniel Pais Ospina; Milton Manotas-Albor; Mario Millan; Edgar Mosquera-Vargas; Mónica Tirado; David Comedi (Environmental Nanotechnology, Monitoring & Management, 2024)

Incorporating uncertainty in Indigenous sea Country monitoring with Bayesian statistics: Towards more informed decision-making - Katherine Cure; Diego R. Barneche; Martial Depczynski; Rebecca Fisher; David J. Warne; James McGree; Jim Underwood; Frank Weisenberger; Elizabeth Evans-Illidge; Brendan Ford; Daniel Oades; Azton Howard; et al. (Ambio, 2024)
Partnerships in marine monitoring combining Traditional Ecological Knowledge and western science are developing globally to improve our understanding of temporal changes in ecological communities that better inform coastal management practices. A fuller communication between scientists and Indigenous partners about the limitations of monitoring results to identify change is essential to the impact of monitoring datasets on decision-making. Here we present a 5-year co-developed case study from a fish monitoring partnership in northwest Australia showing how uncertainty estimated by Bayesian models can be incorporated into monitoring management indicators. Our simulation approach revealed there was high uncertainty in detecting immediate change over the following monitoring year when translated to health performance indicators. Incorporating credibility estimates into health assessments added substantial information to monitoring trends, provided a deeper understanding of monitoring limitations and highlighted the importance of carefully selecting the way we evaluate management performance indicators.

Two-dimensional modeling of CO 2 storage in high heat flow areas: Insights from the Las Tres Virgenes geothermal field, Mexico - Alfonso Reyes-Sandoval; Fernando J. Guerrero; Daniel Pérez-Zárate; Rosa María Prol-Ledesma; Edgar Santoyo (International Journal of Greenhouse Gas Control, 2024)

A differential evolution algorithm for solving mixed-integer nonlinear programming problems - Daniel Molina-Pérez; Efrén Mezura-Montes; Edgar Alfredo Portilla-Flores; Eduardo Vega-Alvarado; Bárbara Calva-Yañez (Swarm and Evolutionary Computation, 2024)

Range-wide phylogeography of the golden jackals (Canis aureus) reveals multiple sources of recent spatial expansion and admixture with dogs at the expansion front - Milomir Stefanović; Wiesław Bogdanowicz; Roya Adavoudi; Francelly Martínez-Sosa; Karolina Doan; Alejandro Flores-Manzanero; Yellapu Srinivas; Ovidiu C. Banea; Duško Ćirović; Gianluca D'Amico; Mihajla Djan; Giorgos Giannatos; et al. (Biological Conservation, 2024)

Antioxidants green tea extract and nordihydroguaiaretic acid confer species and strain-specific lifespan and health effects in Caenorhabditis nematodes - Stephen A. Banse; Christine A. Sedore; Erik Johnson; Anna L. Coleman-Hulbert; Brian Onken; David Hall; E. Grace Jackson; Phu Huynh; Anna C. Foulger; Suzhen Guo; Theo Garrett; Jian Xue; et al. (GeroScience, 2023)
The Caenorhabditis Intervention Testing Program (CITP) is an NIH-funded research consortium of investigators who conduct analyses at three independent sites to identify chemical interventions that reproducibly promote health and lifespan in a robust manner. The founding principle of the CITP is that compounds with positive effects across a genetically diverse panel of Caenorhabditis species and strains are likely engaging conserved biochemical pathways to exert their effects. As such, interventions that are broadly efficacious might be considered prominent compounds for translation for pre-clinical research and human clinical applications. Here, we report results generated using a recently streamlined pipeline approach for the evaluation of the effects of chemical compounds on lifespan and health. We studied five compounds previously shown to extend C. elegans lifespan or thought to promote mammalian health: 17α-estradiol, acarbose, green tea extract, nordihydroguaiaretic acid, and rapamycin. We found that green tea extract and nordihydroguaiaretic acid extend Caenorhabditis lifespan in a species-specific manner. Additionally, these two antioxidants conferred assay-specific effects in some studies—for example, decreasing survival for certain genetic backgrounds in manual survival assays in contrast with extended lifespan as assayed using automated C. elegans Lifespan Machines. We also observed that GTE and NDGA impact on older adult mobility capacity is dependent on genetic background, and that GTE reduces oxidative stress resistance in some Caenorhabditis strains. Overall, our analysis of the five compounds supports the general idea that genetic background and assay type can influence lifespan and health effects of compounds, and underscores that lifespan and health can be uncoupled by chemical interventions.

Rising carbon inequality and its driving factors from 2005 to 2015 - Heran Zheng; Richard Wood; Daniel Moran; Kuishuang Feng; Alexandre Tisserant; Meng Jiang; Edgar G. Hertwich (Global Environmental Change, 2023)

Thermoregulatory ability and mechanism do not differ consistently between neotropical and temperate butterflies - Benita C. Laird‐Hopkins; Esme Ashe‐Jepson; Yves Basset; Stephany Arizala Cobo; Lucy Eberhardt; Inga Freiberga; Josh Hellon; Gwen E. Hitchcock; Irena Kleckova; Daniel Linke; Greg P. A. Lamarre; Alex McFarlane; et al. (Global Change Biology, 2023)
Climate change is a major threat to species worldwide, yet it remains uncertain whether tropical or temperate species are more vulnerable to changing temperatures. To further our understanding of this, we used a standardised field protocol to (1) study the buffering ability (ability to regulate body temperature relative to surrounding air temperature) of neotropical (Panama) and temperate (the United Kingdom, Czech Republic and Austria) butterflies at the assemblage and family level, (2) determine if any differences in buffering ability were driven by morphological characteristics and (3) used ecologically relevant temperature measurements to investigate how butterflies use microclimates and behaviour to thermoregulate. We hypothesised that temperate butterflies would be better at buffering than neotropical butterflies as temperate species naturally experience a wider range of temperatures than their tropical counterparts. Contrary to our hypothesis, at the assemblage level, neotropical species (especially Nymphalidae) were better at buffering than temperate species, driven primarily by neotropical individuals cooling themselves more at higher air temperatures. Morphology was the main driver of differences in buffering ability between neotropical and temperate species as opposed to the thermal environment butterflies experienced. Temperate butterflies used postural thermoregulation to raise their body temperature more than neotropical butterflies, probably as an adaptation to temperate climates, but the selection of microclimates did not differ between regions. Our findings demonstrate that butterfly species have unique thermoregulatory strategies driven by behaviour and morphology, and that neotropical species are not likely to be more inherently vulnerable to warming than temperate species.

Ideal settlement substrate and effect of darkness on spat production of the mangrove cockle Anadara tuberculosa - Edgar Zapata-Vívenes; Daniel Rodríguez-Pesantes; Félix Morales; Sofie Van Den Hende (Aquaculture, 2023)

Identifying fisheries operations in tropical multispecies fisheries: A comparative analysis of multivariate approaches and neural networks - Daniel Quijano; Silvia Salas; Carmen Monroy-García; Michel Dreyfus-León; Edgar Torrres-Irineo (Fisheries Research, 2023)

Contrasting thermal histories in the Dom Feliciano Belt triggered by magmatism related to the Paraná-Etendeka LIP and fracture zone proximity - Edgar do Amaral Santos; Andréa Ritter Jelinek; Daniel Stockli; Frederico Antônio Genezine (Tectonophysics, 2023)

Beneficial effects of selected rhizospheric and endophytic bacteria, inoculated individually or in combination, on non-native host plant development - Alejandro Méndez-Bravo; Lorena C. Herrera-Cornelio; Daniel F. García-Toscano; Ana L. Kiel-Martínez; Edgar Guevara-Avendaño; Mónica Ramírez-Vázquez; Yareli Pérez-Bautista; Alfonso Méndez-Bravo; Frédérique Reverchon (Rhizosphere, 2023)

Evaluation of the Effect of the Application of Combined Pretreatments and Inoculum with High Alkalinity on Food Residues Through BMP Tests - Alanis-Silva Edgar Daniel; Chávez-Parga Ma. Del Carmen; Cortés José Apolinar (BioEnergy Research, 2023)

Verapamil inhibits Kir2.3 channels by binding to the pore and interfering with PIP2 binding - Panagiotis Xynogalos; Ann-Kathrin Rahm; Sebastian Fried; Safak Chasan; Daniel Scherer; Claudia Seyler; Hugo A. Katus; Norbert Frey; Edgar Zitron (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)
The inwardly rectifying potassium current of the cardiomyocyte (I K1 ) is the main determinant of the resting potential. Ion channels Kir2.1, Kir2.2, and Kir2.3 form tetramers and are the molecular correlate of macroscopic I K1 current. Verapamil is an antiarrhythmic drug used to suppress atrial and ventricular arrhythmias. Its primary mechanism of action is via blocking calcium channels. In addition, it has been demonstrated to block I K1 current and the Kir2.1 subunit. Its effect on other subunits that contribute to I K1 current has not been studied to date. We therefore analyzed the effect of verapamil on the Kir channels 2.1, 2.2, and 2.3 in the Xenopus oocyte expression system. Kir2.1, Kir2.2, and Kir2.3 channels were heterologously expressed in Xenopus oocytes. Respective currents were measured with the voltage clamp technique and the effect of verapamil on the current was measured. At a concentration of 300 µM, verapamil inhibited Kir2.1 channels by 41.36% ± 2.7 of the initial current, Kir2.2 channels by 16.51 ± 3.6%, and Kir2.3 by 69.98 ± 4.2%. As a verapamil effect on kir2.3 was a previously unknown finding, we analyzed this effect further. At wash in with 300 µM verapamil, the maximal effect was seen within 20 min of the infusion. After washing out with control solution, there was only a partial current recovery. The current reduction from verapamil was the same at − 120 mV (73.2 ± 3.7%), − 40 mV (85.5 ± 6.5%), and 0 mV (61.5 ± 10.6%) implying no voltage dependency of the block. Using site directed mutations in putative binding sites, we demonstrated a decrease of effect with pore mutant E291A and absence of verapamil effect for D251A. With mutant I214L, which shows a stronger affinity for PIP 2 binding, we observed a normalized current reduction to 61.9 ± 0.06% of the control current, which was significantly less pronounced compared to wild type channels. Verapamil blocks Kir2.1, Kir2.2, and Kir2.3 subunits. In Kir2.3, blockade is dependent on sites E291 and D251 and interferes with activation of the channel via PIP 2 . Interference with these sites and with PIP 2 binding has also been described for other Kir channels blocking drugs. As Kir2.3 is preferentially expressed in atrium, a selective Kir2.3 blocking agent would constitute an interesting antiarrhythmic concept.

Novel MreB inhibitors with antibacterial activity against Gram (-) bacteria - Hye Yeon Sagong; Jesus D. Rosado-Lugo; Eric J. Bryan; Edgar Ferrer-González; Yiling Wang; Yanlu Cao; Ajit K. Parhi; Daniel S. Pilch; Edmond J. LaVoie (Medicinal Chemistry Research, 2022)

Combination with a FtsZ inhibitor potentiates the in vivo efficacy of oxacillin against methicillin-resistant Staphylococcus aureus - Malvika Kaul; Edgar Ferrer-González; Lilly Mark; Ajit K. Parhi; Edmond J. LaVoie; Daniel S. Pilch (Medicinal Chemistry Research, 2022)

Neuroinflammation and galectins: a key relationship in neurodegenerative diseases - Eleazar Ramírez Hernández; Beatriz Alanis Olvera; Daniela Carmona González; Oscar Guerrero Marín; Denisse Pantoja Mercado; Lucero Valencia Gil; Luis F. Hernández-Zimbrón; José Luis Sánchez Salgado; I. Daniel Limón; Edgar Zenteno (Glycoconjugate Journal, 2022)

Global maps of soil temperature - Jonas J. Lembrechts; Johan van den Hoogen; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Julia Kemppinen; Martin Kopecký; Miska Luoto; Ilya M. D. Maclean; Thomas W. Crowther; Joseph J. Bailey; Stef Haesen; et al. (Global Change Biology, 2022)
Research in global change ecology relies heavily on global climatic grids derived from estimates of air temperature in open areas at around 2 m above the ground. These climatic grids do not reflect conditions below vegetation canopies and near the ground surface, where critical ecosystem functions occur and most terrestrial species reside. Here, we provide global maps of soil temperature and bioclimatic variables at a 1‐km 2 resolution for 0–5 and 5–15 cm soil depth. These maps were created by calculating the difference (i.e. offset) between in situ soil temperature measurements, based on time series from over 1200 1‐km 2 pixels (summarized from 8519 unique temperature sensors) across all the world's major terrestrial biomes, and coarse‐grained air temperature estimates from ERA5‐Land (an atmospheric reanalysis by the European Centre for Medium‐Range Weather Forecasts). We show that mean annual soil temperature differs markedly from the corresponding gridded air temperature, by up to 10°C (mean = 3.0 ± 2.1°C), with substantial variation across biomes and seasons. Over the year, soils in cold and/or dry biomes are substantially warmer (+3.6 ± 2.3°C) than gridded air temperature, whereas soils in warm and humid environments are on average slightly cooler (−0.7 ± 2.3°C). The observed substantial and biome‐specific offsets emphasize that the projected impacts of climate and climate change on near‐surface biodiversity and ecosystem functioning are inaccurately assessed when air rather than soil temperature is used, especially in cold environments. The global soil‐related bioclimatic variables provided here are an important step forward for any application in ecology and related disciplines. Nevertheless, we highlight the need to fill remaining geographic gaps by collecting more in situ measurements of microclimate conditions to further enhance the spatiotemporal resolution of global soil temperature products for ecological applications.

Excess heat capacity and entropy of mixing along the hydroxyapatite-chlorapatite and hydroxyapatite-fluorapatite binaries - Edgar Dachs; Artur Benisek; Daniel Harlov; Max Wilke (Physics and Chemistry of Minerals, 2021)
The heat capacity, C p , of synthetic hydroxyapatite [Ca 5 (PO 4 ) 3 OH–OH-Ap], as well as of ten compositions along the OH-Ap-chlorapatite (Cl-Ap) join and 12 compositions along the OH-Ap-fluorapatite (F-Ap) join have been measured using relaxation calorimetry (heat capacity option of the Physical Properties Measurement System—PPMS) and differential scanning calorimetry (DSC) in the temperature range of 5–764 K. Apatites along the Cl-OH and F-OH joins were synthesized at 1100 °C and 300 MPa in an internally heated gas pressure vessel via an exchange process between synthetic fluorapatite or chlorapatite crystals (200–500 μm size) and a series of Ca(OH) 2 -H 2 O solutions with specific compositions and amounts relative to the starting apatite. The standard third-law entropy of OH-Ap, derived from the low-temperature heat capacity measurements, is S ° = 386.3 ± 2.5 J mol −1 K −1 , which is ~ 1% lower than that resulting from low-temperature adiabatic calorimetry data on OH-Ap from the 1950’s. The heat capacity of OH-Ap above 298.15 K shows a hump-shaped anomaly centred around 442 K. Based on published structural and calorimetric work, this feature is interpreted to result from a monoclinic to hexagonal phase transition. Super ambient C p up to this transition can be represented by the polynomial: $$C_{p}^{{\text{OH - Ap}}} {}_{{298K - 442K}}\left( {{\text{J mol}}^{ - 1} {\text{K}}^{- 1}} \right) = {1013.7-13735.5T^{{ - 0.5}}} + 2.616718\,10^{7} T^{{ - 2}} - 3.551381\,10^{9} T^{{ - 3}} .$$ C p OH - Ap 298 K - 442 K J mol - 1 K - 1 = 1013.7 - 13735.5 T - 0.5 + 2.616718 10 7 T - 2 - 3.551381 10 9 T - 3 . . The DSC data above this transition were combined with heat capacities computed using density functional theory and can be given by the C p polynomial: $$C_{p}^{{\text{OH - Ap}}} {}_{{ >\,442K}}\left( {{\text{J mol}}^{ - 1} {\text{K}}^{- 1}} \right) = {877.2-11393.7 T^{ - 0.5}} + {5.452030\,10^{7}} \,T^{- {2}} - {1.394125\,10^{10}} \,T^{- {3}}$$ C p OH - Ap > 442 K J mol - 1 K - 1 = 877.2 - 11393.7 T - 0.5 + 5.452030 10 7 T - 2 - 1.394125 10 10 T - 3 . Positive excess heat capacities of mixing, ∆ C p ex , in the order of 1–2 J mol −1 K −1 , occur in both solid solutions at around 70 K. They are significant at these conditions exceeding the 2σ-uncertainty of the data. This positive ∆ C p ex is compensated by a negative ∆ C p ex of the same order at around 250 K in both binaries. At higher temperatures (up to 1200 K), ∆ C p ex is zero within error for all solid solution members. As a consequence, the calorimetric entropies, S cal , show no deviation from ideal mixing behaviour within a 2σ-uncertainty for both joins. Excess entropies of mixing, ∆S ex , are thus zero for the OH-Ap–F-Ap, as well as for the OH-Ap–Cl-Ap join. The C p – T behaviour of the OH-Ap endmember is discussed in relation to that of the F- and Cl-endmembers.

Spatial Dynamics Modeling of Small-Scale Fishing Fleets With a Random Walk Approach - Daniel R. Quijano Quiñones; Jorge A. López-Rocha; Isis Hernández-Herrera; Edgar Torres-Irineo (Frontiers in Marine Science, 2021)
The understanding of fishing effort allocation has been recognized as a key feature within the spatial management planning of fisheries. In small-scale fisheries this assessment is challenging because of their multi-specific context. This has resulted in management regulations that do not fulfill their objectives. Therefore, the analysis of vessels movement is needed for the better assessment and management of small-scale fisheries. Thus, we used a Random Walk (RW) modeling approach to characterize the fishing trips of small-scale multi-gear vessels targeting multiple species. We analyzed activities of three different gears (hand net, handline, longline) and two fishing methods (diving, “gareteo”) recorded with a GPS from 156 fishing trips along three fishing seasons (2018–2020) by the small-scale fleet of Yucatan, Mexico. We fitted seven RW models for the movement data and compared their relative and absolute fit through a delta Akaike test and G-Tests respectively. A total of 143 trajectories showed conclusive evidence to establish a CCRW-type movement; the remaining 13 trajectories fit three models (CCRW, TRW and CRW). The Random Walk models were useful for modeling a multi-gear, small-scale fleet operating in southeast Mexico. According to our results, the Composite Correlated Model was the most suitable RW for this fleet. For future studies, we suggest increasing the number of fishing trips and conducting specific studies by gear and fishing method. Also, the application of relative and absolute fit tests to compare the performance of RW models is highly recommended.

Spatio-Temporal Determination of Small-Scale Vessels’ Fishing Grounds Using a Vessel Monitoring System in the Southeastern Gulf of Mexico - Edgar Torres-Irineo; Silvia Salas; Jorge Iván Euán-Ávila; Leopoldo E. Palomo; Daniel R. Quijano Quiñones; Eva Coronado; Rocío Joo (Frontiers in Marine Science, 2021)
In most small-scale fisheries (SSF), there is limited or null information about the distribution and spatial extent of the fishing grounds where the fleets operate, due to the lack of explicit spatial and temporal data. This information is key when addressing marine spatial planning and fisheries management programs for SSF. In addition to technical or biogeographic restrictions, environmental conditions in the area influence the way fishers operate. Making use of data from a pilot Vessel Monitoring System (VMS) project tested in a small-scale fleet in the Southeastern Gulf of Mexico (SGoM), for the first time in the region, we were able to learn what role environmental factors play in the distribution of potential fishing grounds for this fleet. We got tracking information of 1,608 daily fishing trips from vessels operating in four states using the VMS for 7 months. We used a correlative modeling approach to identify potential fishing grounds where this fleet operates along the SGoM, accounting for environmental variables. We assumed that environmental conditions can shape the spatial distribution of species targeted by this fleet and hence influence fishers’ operations. The results indicated that net primary production and sea surface temperature were the main drivers that shape the spatio-temporal potential distribution of fishing grounds in the study site. The approach employed here seems appropriated and opens an opportunity to learn more about the factors that define the spatial distribution of small-scale fleets and their potential fishing grounds.

Comparative proteomic analysis of outer membrane vesicles from Brucella suis, Brucella ovis, Brucella canis and Brucella neotomae - María del Socorro Ruiz-Palma; Eric Daniel Avila-Calderón; Ma. Guadalupe Aguilera-Arreola; Ahidé López-Merino; Enrico A. Ruiz; María del Rosario Morales-García; Edgar Oliver López-Villegas; Zulema Gomez-Lunar; Beatriz Arellano-Reynoso; Araceli Contreras-Rodríguez (Archives of Microbiology, 2021)

Antifungal Activity In Vitro and In Vivo of Mesquite Extract (Prosopis glandulosa) Against Phytopathogenic Fungi - Arely Nohemí López-Anchondo; Daniel López-de la Cruz; Edgar Gutiérrez-Reyes; José Cristobal Castañeda-Ramírez; Norma Margarita De la Fuente-Salcido (Indian Journal of Microbiology, 2021)

Challenges for Restoration of Coastal Marine Ecosystems in the Anthropocene - Avigdor Abelson; Daniel C. Reed; Graham J. Edgar; Carter S. Smith; Gary A. Kendrick; Robert J. Orth; Laura Airoldi; Brian Silliman; Michael W. Beck; Gesche Krause; Nadav Shashar; Noga Stambler; et al. (Frontiers in Marine Science, 2020)

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

Full genome sequence of the first SARS-CoV-2 detected in Mexico - Fabiola Garcés-Ayala; Adnan Araiza-Rodríguez; Edgar Mendieta-Condado; Abril Paulina Rodríguez-Maldonado; Claudia Wong-Arámbula; Magaly Landa-Flores; Juan Carlos del Mazo-López; Maribel González-Villa; Noé Escobar-Escamilla; David Esaú Fragoso-Fonseca; María del Carmen Esteban-Valencia; Lourdes Lloret-Sánchez; et al. (Archives of Virology, 2020)

Valorization of the filamentous seaweed Chaetomorpha gracilis (Cladophoraceae, Chlorophyta) from an IMTA system - Yolanda Freile-Pelegrín; Cresencia Chávez-Quintal; Edgar Caamal-Fuentes; Erika Vázquez-Delfín; Tomás Madera-Santana; Daniel Robledo (Journal of Applied Phycology, 2020)

Automated lifespan determination across Caenorhabditis strains and species reveals assay-specific effects of chemical interventions - Stephen A. Banse; Mark Lucanic; Christine A. Sedore; Anna L. Coleman-Hulbert; W. Todd Plummer; Esteban Chen; Jason L. Kish; David Hall; Brian Onken; Michael P. Presley; E. Grace Jones; Benjamin W. Blue; et al. (GeroScience, 2019)
The goal of the Caenorhabditis Intervention Testing Program is to identify robust and reproducible pro-longevity interventions that are efficacious across genetically diverse cohorts in the Caenorhabditis genus. The project design features multiple experimental replicates collected by three different laboratories. Our initial effort employed fully manual survival assays. With an interest in increasing throughput, we explored automation with flatbed scanner-based Automated Lifespan Machines (ALMs). We used ALMs to measure survivorship of 22 Caenorhabditis strains spanning three species. Additionally, we tested five chemicals that we previously found extended lifespan in manual assays. Overall, we found similar sources of variation among trials for the ALM and our previous manual assays, verifying reproducibility of outcome. Survival assessment was generally consistent between the manual and the ALM assays, although we did observe radically contrasting results for certain compound interventions. We found that particular lifespan outcome differences could be attributed to protocol elements such as enhanced light exposure of specific compounds in the ALM, underscoring that differences in technical details can influence outcomes and therefore interpretation. Overall, we demonstrate that the ALMs effectively reproduce a large, conventionally scored dataset from a diverse test set, independently validating ALMs as a robust and reproducible approach toward aging-intervention screening.

Sediment provenance, sediment-dispersal systems, and major arc-magmatic events recorded in the Mexican foreland basin, North-Central and Northeastern Mexico - Edgar Juárez-Arriaga; Timothy F. Lawton; Yam Zul E. Ocampo-Díaz; Daniel F. Stockli; Luigi Solari (International Geology Review, 2019)

Corrigendum: A Response to Scientific and Societal Needs for Marine Biological Observations - Nicholas J. Bax; Patricia Miloslavich; Frank Edgar Muller-Karger; Valerie Allain; Ward Appeltans; Sonia Dawn Batten; Lisandro Benedetti-Cecchi; Pier Luigi Buttigieg; Sanae Chiba; Daniel Paul Costa; J. Emmett Duffy; Daniel C. Dunn; et al. (Frontiers in Marine Science, 2019)

A Response to Scientific and Societal Needs for Marine Biological Observations - Nicholas J. Bax; Patricia Miloslavich; Frank Edgar Muller-Karger; Valerie Allain; Ward Appeltans; Sonia Dawn Batten; Lisandro Benedetti-Cecchi; Pier Luigi Buttigieg; Sanae Chiba; Daniel Paul Costa; J. Emmett Duffy; Daniel C. Dunn; et al. (Frontiers in Marine Science, 2019)

NEOTROPICAL XENARTHRANS: a data set of occurrence of xenarthran species in the Neotropics - Paloma Marques Santos; Adriana Bocchiglieri; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adryelle Moreira; Agnis Cristiane de Souza; Agustin Manuel Abba; Agustin Paviolo; Ailin Gatica; Akyllan Zoppi Medeiro; Alan Nilo Costa; Alberto Gonzalez Gallina; et al. (Ecology, 2019)
Xenarthrans—anteaters, sloths, and armadillos—have essential functions for ecosystem maintenance, such as insect control and nutrient cycling, playing key roles as ecosystem engineers. Because of habitat loss and fragmentation, hunting pressure, and conflicts with domestic dogs, these species have been threatened locally, regionally, or even across their full distribution ranges. The Neotropics harbor 21 species of armadillos, 10 anteaters, and 6 sloths. Our data set includes the families Chlamyphoridae (13), Dasypodidae (7), Myrmecophagidae (3), Bradypodidae (4), and Megalonychidae (2). We have no occurrence data on Dasypus pilosus (Dasypodidae). Regarding Cyclopedidae, until recently, only one species was recognized, but new genetic studies have revealed that the group is represented by seven species. In this data paper, we compiled a total of 42,528 records of 31 species, represented by occurrence and quantitative data, totaling 24,847 unique georeferenced records. The geographic range is from the southern United States, Mexico, and Caribbean countries at the northern portion of the Neotropics, to the austral distribution in Argentina, Paraguay, Chile, and Uruguay. Regarding anteaters, Myrmecophaga tridactyla has the most records ( n = 5,941), and Cyclopes sp. have the fewest ( n = 240). The armadillo species with the most data is Dasypus novemcinctus ( n = 11,588), and the fewest data are recorded for Calyptophractus retusus ( n = 33). With regard to sloth species, Bradypus variegatus has the most records ( n = 962), and Bradypus pygmaeus has the fewest ( n = 12). Our main objective with Neotropical Xenarthrans is to make occurrence and quantitative data available to facilitate more ecological research, particularly if we integrate the xenarthran data with other data sets of Neotropical Series that will become available very soon (i.e., Neotropical Carnivores, Neotropical Invasive Mammals, and Neotropical Hunters and Dogs). Therefore, studies on trophic cascades, hunting pressure, habitat loss, fragmentation effects, species invasion, and climate change effects will be possible with the Neotropical Xenarthrans data set. Please cite this data paper when using its data in publications. We also request that researchers and teachers inform us of how they are using these data.

Geodiversity Mapping and Relationship with Vegetation: A Regional-Scale Application in SE Brazil - Daniel Souza dos Santos; Kátia Leite Mansur; Elias Ribeiro de Arruda Jr; Marcelo Eduardo Dantas; Edgar Shinzato (Geoheritage, 2019)

Urinary metabolites of the UV filter octocrylene in humans as biomarkers of exposure - Daniel Bury; Hendrik Modick-Biermann; Edgar Leibold; Thomas Brüning; Holger M. Koch (Archives of Toxicology, 2019)

BioTIME: A database of biodiversity time series for the Anthropocene - Maria Dornelas; Laura H. Antão; Faye Moyes; Amanda E. Bates; Anne E. Magurran; Dušan Adam; Asem A. Akhmetzhanova; Ward Appeltans; José Manuel Arcos; Haley Arnold; Narayanan Ayyappan; Gal Badihi; et al. (Global Ecology and Biogeography, 2018)
Motivation The BioTIME database contains raw data on species identities and abundances in ecological assemblages through time. These data enable users to calculate temporal trends in biodiversity within and amongst assemblages using a broad range of metrics. BioTIME is being developed as a community‐led open‐source database of biodiversity time series. Our goal is to accelerate and facilitate quantitative analysis of temporal patterns of biodiversity in the Anthropocene. Main types of variables included The database contains 8,777,413 species abundance records, from assemblages consistently sampled for a minimum of 2 years, which need not necessarily be consecutive. In addition, the database contains metadata relating to sampling methodology and contextual information about each record. Spatial location and grain BioTIME is a global database of 547,161 unique sampling locations spanning the marine, freshwater and terrestrial realms. Grain size varies across datasets from 0.0000000158 km 2 (158 cm 2 ) to 100 km 2 (1,000,000,000,000 cm 2 ). Time period and grain BioTIME records span from 1874 to 2016. The minimal temporal grain across all datasets in BioTIME is a year. Major taxa and level of measurement BioTIME includes data from 44,440 species across the plant and animal kingdoms, ranging from plants, plankton and terrestrial invertebrates to small and large vertebrates. Software format .csv and .SQL.

Prioritizing Consumption‐Based Carbon Policy Based on the Evaluation of Mitigation Potential Using Input‐Output Methods - Richard Wood; Daniel Moran; Konstantin Stadler; Diana Ivanova; Kjartan Steen‐Olsen; Alexandre Tisserant; Edgar G. Hertwich (Journal of Industrial Ecology, 2018)
Summary Carbon footprints aim to engage consumers in contributing to climate‐change mitigation. Consumption‐oriented policy measures attempt to cause voluntary or incentivized interventions that reduce environmental impact through the supply chain by utilizing demand drivers. A large body of life cycle assessment studies describe how specific actions can reduce the environmental footprint of an individual or household. However, these assessments are often conducted with a narrow focus on particular goods and processes. Here, we formalize a counterfactual method and operational tool for scoping the potential impact of such actions, focusing on economy‐wide impact. This “quickscan” tool can model shifts and reductions in demand, rebound effects (using marginal expenditure), changes in domestic and international production recipes, and reductions in the environmental intensity of production. This tool provides quick, macro‐level estimates of the efficacy of consumer‐oriented policy measures and can help to prioritize relevant policies. We demonstrate the method using two case studies on diet and clothing using the EXIOBASE3 multiregional input‐output database, giving spatially explicit information on where environmental impact reductions of the interventions occur, and where impacts may increase in the case of rebounds.

Growth, biochemical and antioxidant content of Rhodymenia pseudopalmata (Rhodymeniales, Rhodophyta) cultivated under salinity and irradiance treatments - Hugo Pliego-Cortés; Edgar Caamal-Fuentes; Jorge Montero-Muñoz; Yolanda Freile-Pelegrín; Daniel Robledo (Journal of Applied Phycology, 2017)

Cophylogenetic signal is detectable in pollination interactions across ecological scales - Matthew C. Hutchinson; Edgar Fernando Cagua; Daniel B. Stouffer (Ecology, 2017)
That evolutionary history can influence the way that species interact is a basic tenet of evolutionary ecology. However, when the role of evolution in determining ecological interactions is investigated, focus typically centers on just one side of the interaction. A cophylogenetic signal, the congruence of evolutionary history across both sides of an ecological interaction, extends these previous explorations and provides a more complete picture of how evolutionary patterns influence the way species interact. To date, cophylogenetic signal has most typically been studied in interactions that occur between fine taxonomic clades that show high intimacy. In this study, we took an alternative approach and made an exhaustive assessment of cophylogeny in pollination interactions. To do so, we assessed the strength of cophylogenetic signal at four distinct scales of pollination interaction: (1) across plant–pollinator associations globally, (2) in local pollination communities, (3) within the modular structure of those communities, and (4) in individual modules. We did so using a globally distributed dataset comprised of 54 pollination networks, over 4000 species, and over 12,000 interactions. Within these data, we detected cophylogenetic signal at all four scales. Cophylogenetic signal was found at the level of plant–pollinator interactions on a global scale and in the majority of pollination communities. At the scale defined by the modular structure within those communities, however, we observed a much weaker cophylogenetic signal. Cophylogenetic signal was detectable in a significant proportion of individual modules and most typically when within‐module phylogenetic diversity was low. In sum, the detection of cophylogenetic signal in pollination interactions across scales provides a new dimension to the story of how past evolution shapes extant pollinator–angiosperm interactions.

Inhibition of inwardly rectifying Kir2.x channels by the novel anti-cancer agent gambogic acid depends on both pore block and PIP2 interference - Daniel Scherer; Benedikt Schworm; Claudia Seyler; Panagiotis Xynogalos; Eberhard P. Scholz; Dierk Thomas; Hugo A. Katus; Edgar Zitron (Naunyn-Schmiedeberg's Archives of Pharmacology, 2017)

Role of plasma membrane-associated AKAPs for the regulation of cardiac IK1 current by protein kinase A - Claudia Seyler; Daniel Scherer; Christoph Köpple; Martin Kulzer; Sevil Korkmaz; Panagiotis Xynogalos; Dierk Thomas; Ziya Kaya; Eberhard Scholz; Johannes Backs; Christoph Karle; Hugo A. Katus; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2017)

Adaptive responses of tropical tuna purse-seiners under temporal regulations - Edgar Torres-Irineo; Michel Dreyfus-León; Daniel Gaertner; Silvia Salas; Paul Marchal (Ambio, 2017)

Toward a Practical Ontology for Socioeconomic Metabolism - Stefan Pauliuk; Guillaume Majeau‐Bettez; Daniel B. Müller; Edgar G. Hertwich (Journal of Industrial Ecology, 2016)
Summary The complexity of data and methods in industrial ecology (IE) keeps growing, and the demand for comprehensive and interdisciplinary assessments increases. To keep up with this development, the field needs a data infrastructure that allows researchers to annotate, store, retrieve, combine, and exchange data at low cost, without loss of information, and across disciplines and model frameworks. A consensus‐building debate about how to describe the common object of study, socioeconomic metabolism (SEM), is necessary for the development of practical data structures and databases. We review the definitions of basic concepts to describe SEM in IE and related fields such as integrated assessment modeling. We find that many definitions are not compatible, are implicit, and are sometimes lacking. To resolve the conflicts and inconsistencies within the current definitions, we propose a hierarchical system of terms and definitions, a practical ontology , for describing objects, their properties, and events in SEM. We propose a typology of object properties and use sets to group objects into a hierarchical, mutually exclusive, and collectively exhaustive (H‐MECE) classification. This grouping leads to a general definition of stocks . We show that a MECE representation of events necessarily requires two complementary concepts: processes and flows , for which we propose general definitions based on sets. Using these definitions, we show that the system structure of any interdisciplinary model of SEM can be formulated as a directed graph . We propose guidelines for semantic data annotation and database design, which can help to turn the vision of a powerful data infrastructure for SEM research into reality.

Distinct pro-vigilant profile induced in rats by the mGluR5 potentiator LSN2814617 - Sally Loomis; Andrew McCarthy; Christopher Baxter; Daniel O. Kellett; Dale M. Edgar; Mark Tricklebank; Gary Gilmour (Psychopharmacology, 2015)

Preclinical Pharmacokinetic/Pharmacodynamic Modeling and Simulation in the Pharmaceutical Industry: An IQ Consortium Survey Examining the Current Landscape - Edgar Schuck; Tonika Bohnert; Arijit Chakravarty; Valeriu Damian-Iordache; Christopher Gibson; Cheng-Pang Hsu; Tycho Heimbach; Anu Shilpa Krishnatry; Bianca M Liederer; Jing Lin; Tristan Maurer; Jerome T Mettetal; et al. (The AAPS Journal, 2015)

Roles of bacterial membrane vesicles - Eric Daniel Avila-Calderón; Minerva Georgina Araiza-Villanueva; Juan Carlos Cancino-Diaz; Edgar Oliver López-Villegas; Nammalwar Sriranganathan; Stephen M. Boyle; Araceli Contreras-Rodríguez (Archives of Microbiology, 2015)

Class III antiarrhythmic drug dronedarone inhibits cardiac inwardly rectifying Kir2.1 channels through binding at residue E224 - Panagiotis Xynogalos; Claudia Seyler; Daniel Scherer; Christoph Koepple; Eberhard P. Scholz; Dierk Thomas; Hugo A. Katus; Edgar Zitron (Naunyn-Schmiedeberg's Archives of Pharmacology, 2014)

Over 75 years of zooplankton data from Australia - Claire H. Davies; Amelia J. Armstrong; Mark Baird; Frank Coman; Steven Edgar; Daniel Gaughan; Jack Greenwood; Felipe Gusmão; Natasha Henschke; J. Anthony Koslow; Sophie C. Leterme; A. David McKinnon; et al. (Ecology, 2014)
Zooplankton are the key trophic link between primary producers and fish in pelagic ecosystems. Historically, there are few zooplankton time series in Australia, with no data sets longer than two years prior to 2008. Here we compile 98 676 abundance records of more than 1000 zooplankton taxa from unpublished research cruises, student projects, published literature, and the recent Integrated Marine Observing System (IMOS). This data set covers the entire coastal and shelf region of Australia and dates back to 1938. Most records are for copepods, but there are also data for other taxa such as decapods, chaetognaths, thaliaceans, appendicularians, and cladocerans. Metadata are provided for each record, including dates, coordinates, and information on mesh size and sampling methods. To facilitate analysis across the multiple data sets, we have updated the species names according to the World Register of Marine Species (WoRMS) and converted units to abundance per cubic meter. These data will be valuable for studies of biodiversity, biogeography, impacts of climate change, and ecosystem health. We encourage researchers holding additional Australian zooplankton data to contact us and contribute their data to the data set so we can periodically publish updates.

Bycatch species composition over time by tuna purse-seine fishery in the eastern tropical Atlantic Ocean - Edgar Torres-Irineo; Monin Justin Amandè; Daniel Gaertner; Alicia Delgado de Molina; Hilario Murua; Pierre Chavance; Javier Ariz; Jon Ruiz; Nerea Lezama-Ochoa (Biodiversity and Conservation, 2014)

Life cycle assessment of an offshore grid interconnecting wind farms and customers across the North Sea - Anders Arvesen; Rasmus Nikolai Nes; Daniel Huertas-Hernando; Edgar G. Hertwich (The International Journal of Life Cycle Assessment, 2014)

Symptoms of anxiety and mood disturbance alter cardiac and peripheral autonomic control in patients with metabolic syndrome - Edgar Toschi-Dias; Ivani C. Trombetta; Valdo José Dias da Silva; Cristiane Maki-Nunes; Maria Janieire N. N. Alves; Luciana F. Angelo; Felipe X. Cepeda; Daniel G. Martinez; Carlos Eduardo Negrão; Maria Urbana P. B. Rondon (European Journal of Applied Physiology, 2013)

Long‐term shifts in abundance and distribution of a temperate fish fauna: a response to climate change and fishing practices - Peter R. Last; William T. White; Daniel C. Gledhill; Alistair J. Hobday; Rebecca Brown; Graham J. Edgar; Gretta Pecl (Global Ecology and Biogeography, 2011)
Aim South‐eastern Australia is a climate change hotspot with well‐documented recent changes in its physical marine environment. The impact on and temporal responses of the biota to change are less well understood, but appear to be due to influences of climate, as well as the non‐climate related past and continuing human impacts. We attempt to resolve the agents of change by examining major temporal and distributional shifts in the fish fauna and making a tentative attribution of causal factors. Location Temperate seas of south‐eastern Australia. Methods Mixed data sources synthesized from published accounts, scientific surveys, spearfishing and angling competitions, commercial catches and underwater photographic records, from the ‘late 1800s’ to the ‘present’, were examined to determine shifts in coastal fish distributions. Results Forty‐five species, representing 27 families (about 30% of the inshore fish families occurring in the region), exhibited major distributional shifts thought to be climate related. These are distributed across the following categories: species previously rare or unlisted (12), with expanded ranges (23) and/or abundance increases (30), expanded populations in south‐eastern Tasmania (16) and extra‐limital vagrants (4). Another 9 species, representing 7 families, experienced longer‐term changes (since the 1800s) probably due to anthropogenic factors, such as habitat alteration and fishing pressure: species now extinct locally (3), recovering (3), threatened (2) or with remnant populations (1). One species is a temporary resident periodically recruited from New Zealand. Of fishes exhibiting an obvious poleward movement, most are reef dwellers from three Australian biogeographic categories: widespread southern, western warm temperate (Flindersian) or eastern warm temperate (Peronian) species. Main conclusions Some of the region's largest predatory reef fishes have become extinct in Tasmanian seas since the ‘late 1800s’, most likely as a result of poor fishing practices. In more recent times, there have been major changes in the distribution patterns of Tasmanian fishes that correspond to dramatic warming observed in the local marine environment.

Excess heat capacity and entropy of mixing along the chlorapatite–fluorapatite binary join - Edgar Dachs; Daniel Harlov; Artur Benisek (Physics and Chemistry of Minerals, 2010)

Pflanzen neu entdecken: Rheinauer Thesen zu Rechten von Pflanzen - Florianne Koechlin; Daniel Ammann; Eva Gelinsky; Benny Haerlin; Martin Ott; Beat Sitter-Liver; Werner Stumpf; Edgar Wagner; Amadeus Zschunke; Günter Altner; Nikolai Fuchs; A. Heistinger; et al. (Journal of Consumer Protection and Food Safety, 2009)

Refixation stability in shoulder hemiarthroplasty in case of four-part proximal humeral fracture - Daniel Baumgartner; Silvio René Lorenzetti; Robert Mathys; Beat Gasser; Edgar Stüssi (Medical & Biological Engineering & Computing, 2009)

Inhibition of cardiac hERG potassium channels by tetracyclic antidepressant mianserin - Daniel Scherer; Katharina von Löwenstern; Edgar Zitron; Eberhard P. Scholz; Ramona Bloehs; Sven Kathöfer; Dierk Thomas; Alexander Bauer; Hugo A. Katus; Christoph A. Karle; Claudia Kiesecker (Naunyn-Schmiedeberg's Archives of Pharmacology, 2008)

Anticholinergic antiparkinson drug orphenadrine inhibits HERG channels: block attenuation by mutations of the pore residues Y652 or F656 - Eberhard P. Scholz; Franziska M. Konrad; Daniel L. Weiss; Edgar Zitron; Claudia Kiesecker; Ramona Bloehs; Martin Kulzer; Dierk Thomas; Sven Kathöfer; Alexander Bauer; Martin H. Maurer; Gunnar Seemann; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2007)

Activation of inwardly rectifying Kir2.x potassium channels by β3-adrenoceptors is mediated via different signaling pathways with a predominant role of PKC for Kir2.1 and of PKA for Kir2.2 - Daniel Scherer; Claudia Kiesecker; Martin Kulzer; Myriam Günth; Eberhard P. Scholz; Sven Kathöfer; Dierk Thomas; Martin Maurer; Jörg Kreuzer; Alexander Bauer; Hugo A. Katus; Christoph A. Karle; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2007)

Regulation of cardiac inwardly rectifying potassium current IK1 and Kir2.x channels by endothelin-1 - Claudia Kiesecker; Edgar Zitron; Daniel Scherer; Sonja Lueck; Ramona Bloehs; Eberhard P. Scholz; Marcus Pirot; Sven Kathöfer; Dierk Thomas; Volker A. W. Kreye; Johann Kiehn; Mathias M. Borst; et al. (Journal of Molecular Medicine, 2006)

Toluidine blue-O staining of prion protein deposits - Aurora Sánchez; Aída Guzmán; Alma Ortiz; Daniel Rembao; Blanca Espinosa; Edgar Zenteno; Jorge Guevara (Histochemistry and Cell Biology, 2001)